Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/978-3-642-54816-1_17
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Nintendo Wii in Motor Rehabilitation for Virtual Reality Interventions: A Literature Review

Abstract: Several review articles have been published on the use of Virtual Reality (VR) in motor rehabilitation. The majority of these focus on the effectiveness of VR on improving motor function using relatively expensive commercial tools and technologies including robotics, cybergloves, cybergrasps, joysticks, force sensors and motion capture systems. However, we present the case in this chapter that game sensors and VR technologies which can be customized and reconfigured,such as the Nintendo Wii, provide an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…Gaming technologies such as Microsoft Kinect and Nintendo Wii have been widely used for 'exergames', a term underpinning games for physiotherapeutic exercising, and for a broad range of neurophysiological conditions. Previous research by the authors showed promising results with engagement and effectiveness of the intervention for stroke rehabilitation using customised VR games and gaming sensors [18] [25]. Accordingly, there are many opportunities for the applicability of VR and gaming technologies to pain related interventions.…”
Section: Commercial Game Devices In Pain Carementioning
confidence: 97%
“…Gaming technologies such as Microsoft Kinect and Nintendo Wii have been widely used for 'exergames', a term underpinning games for physiotherapeutic exercising, and for a broad range of neurophysiological conditions. Previous research by the authors showed promising results with engagement and effectiveness of the intervention for stroke rehabilitation using customised VR games and gaming sensors [18] [25]. Accordingly, there are many opportunities for the applicability of VR and gaming technologies to pain related interventions.…”
Section: Commercial Game Devices In Pain Carementioning
confidence: 97%
“…This system uses MS Kinect as input and several biosignal acquisition devices to capture full-body motion while the game is in progress. Finally, a recently published literature review [23] analyzes 69 of the most important proposals for health care that use Wii for motor rehabilitation. One of the conclusions of this study is that one of the potentials that should be explored is the development of new games customized to individual needs.…”
Section: Related Workmentioning
confidence: 99%
“…The motion data are transmitted to the local terminal via Bluetooth or over the Internet. The input technology needs to be of established accuracy as the data captured needs to illustrate and monitor the SU's performance effectively [12]. The motion data are sent over the internet to the clinician platform, as seen in [11].…”
Section: Figure 1 Schematic Diagram Of the Proposed Frameworkmentioning
confidence: 99%
“…The issues created by an ageing population [8], highlight the need for implementation of evidence-based, innovative approaches to empower the service users (SUs) and families to support a continuum of health provision and care; and at the same time, relieve the ever-increasing pressure on respective governmental bodies to provide these services in more cost-efficient ways [9], [10]. Such a sustainable health system, would only be realised by the empowerment of the clinical professional and SU to utilise recently research-evidenced interventions, such as SGs for rehabilitation [11], [12], to create a home-based quiver of solutions and interventions that can be fully customised to fit the rehabilitation targets at request. Customisation needs to take place in all aspects of the design of such interventions, including the therapy regime that needs to be aligned with the game mechanics to maximise the effectiveness of the intervention [13]- [15].…”
Section: Introductionmentioning
confidence: 99%